Telomere length in vascular tissues from patients with atherosclerotic disease - Nzietchueng, R.; Elfarra, M.; Nloga, J.; Labat, C.; Carteaux, J.P.; Maureira, P.; Lacolley, P.; Villemot, J.P.; Benetos, A. (The Journal of nutrition, health & aging, 2011)
The present study was aimed at evaluating telomere length in blood and in different vascular tissues with or without atheroma, in 3 groups of subjects: a group of atherosclerotic subjects who underwent surgery (Atherosclerosis-Surgery), a second group of subjects with asymptomatic atherosclerotic carotid plaques but who did not undergo cardiovascular surgery (Atherosclerosis-No surgery), and a third group of subjects without atherosclerotic disease (Controls). The main objective was to determine if there is in vivo regulation of telomere length in situ by atherosclerotic lesions. A total of 84 subjects (mean age 69±8 years) were studied. Blood and arterial tissue telomere lengths were determined by Southern blotting. Personal medical history (diabetes, hypertension, cardiovascular disease, dyslipidemia), family medical history, drug intake, and lifestyle were evaluated in the entire population through the use of a questionnaire. Arterial segments which did not develop atherosclerosis such as the saphenous vein and internal mammary artery, had longer telomere length than aortic segments. On the other hand, telomere length was shorter in aortic tissues which presented atherosclerotic lesions compared to corresponding tissues without atherosclerotic lesions. These results also suggest tissue regulation of telomere size by local factors likely related to oxidative stress responses.